2010
DOI: 10.1111/j.1601-183x.2010.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of the 11p13 locus on developmental verbal dyspraxia and EEG centrotemporal sharp waves

Abstract: We recently showed genomewide linkage of centrotemporal sharp waves (CTS) in classic Rolandic epilepsy (RE) families to chromosome 11p13, and fine-mapped this locus to variants in the ELP4 gene. Speech sound disorder (SSD) is a common comorbidity in RE subjects, of unknown etiology, which co-aggregates in family members in a manner that could hypothetically be explained by shared underlying genetic risk with CTS. Furthermore, the neural mechanism of SSD is unknown, although individuals with rare, Mendelian for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 41 publications
3
49
0
4
Order By: Relevance
“…We hypothesized that as has been found for a number of complex neurodevelopmental disorders (eg, autism), 6,34 intellectual disability, 35,36 and schizophrenia, 37 rare CNVs in genomic DNA may be associated with increased risk for CAS. Consistent with this hypothesis, array comparative genomic hybridization analyses identified 16p11.2 deletions in two patients with CAS in the same approximate region as reported for other patients with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that as has been found for a number of complex neurodevelopmental disorders (eg, autism), 6,34 intellectual disability, 35,36 and schizophrenia, 37 rare CNVs in genomic DNA may be associated with increased risk for CAS. Consistent with this hypothesis, array comparative genomic hybridization analyses identified 16p11.2 deletions in two patients with CAS in the same approximate region as reported for other patients with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging genomic studies have begun to report that speech impairment consistent with CAS is associated with several genes and loci for epilepsy, including FOXP1, 34,38 FOXG1, 39 ELP4, 36 and RAI1. 40 CAS and epilepsy may have common neurogenetic substrates associated with 16p11.2 deletions or they may co-segregate as separate traits.…”
Section: Discussionmentioning
confidence: 99%
“…При обследовании 36 пациентов с роландической эпилепсией U. Stephani и G. Carlsson [39] не обнаружили у них корреляции между выраженностью изменений на ЭЭГ и показателями IQ, однако у каждого пациента от-мечалось хотя бы одно из нарушений: дискалькулия, от-ставание в развитии речи, СДВГ, расстройство координа-ции, зрительно-пространственные нарушения. Генетиче-ские исследования в 38 семьях, в которых у пробанда была подтверждена роландическая эпилепсия, показали плейо-тропный эффект локуса 11p13, который детерминирует и речевые нарушения, и ЭЭГ-паттерн заболевания [40].…”
Section: журнал неврологии и психиатрии 3 2016 обзорыunclassified
“…In this study evidence for linkage to chromosome 15q14 was obtained with a maximal LOD score of 3.56 under an autosomal recessive mode of inheritance but no mutation was identified. Similarly in other recent studies despite promising logarithm of odds (LOD) scores, no genetic mutations have been identified [31,32]. Recent studies in some families has shown an overlap between epileptic encephalopathy with CSWS, atypical benign partial epilepsy, and BECTS which has led to the concept of a spectrum of epilepsy-aphasia disorders with BECTS at the lower end, the broad less well-defined group of epilepsy-aphasia children in the middle, and classical LKS and the syndrome of CSWS at the extreme end [30,[33][34][35].…”
Section: Geneticsmentioning
confidence: 99%